Segregation of rol Genes in Two Generations of Sinningia speciosa Engineered Through Wild Type Rhizobium rhizogenes - Desmet, Siel; Dhooghe, Emmy; De Keyser, Ellen; Quataert, Paul; Eeckhaut, Tom; Van Huylenbroeck, Johan; Geelen, Danny (Frontiers in Plant Science, 2020)
Rhizobium rhizogenes infects and transforms a wide range of plant species. It thereby introduces new genes located on transfer-DNA of the root inducing plasmid (pRi) into the plant genome and one of its abilities is to alter the host root system. Explants from pRi transformed roots from Sinningia speciosa were regenerated to create naturally transgenic Ri lines. The presence of rol and aux genes in the Ri lines was linked with altered growth characteristics: shorter peduncles, wrinkled leaves, delayed flowering and enhanced root growth. The potential of Ri lines for breeding was evaluated through consecutive backcrossing with the original host genotype. The progeny of reciprocal crosses showed non-Mendelian inheritance suggesting partial transmission of the of the aux and rol genes. The typical Ri phenotype observed in the primary Ri line was partially inherited. These results revealed that the Ri phenotype is a complex trait influenced by the genetic background of the Ri line.